Self-Regulation Predictability on Active and Passive Procrastination Among Academics in Higher Education - Bhusal, Navraj; Bhattarai, Raj Kumar (New Perspective: Journal of Business and Economics, 2025)
The study investigates the predictive role of self-regulation on active and passive procrastinatory behaviors among higher education academics. Data were collected through a survey of 409 respondents and analyzed using descriptive and inferential statistical methods. The findings reveal that self-regulation significantly influences both types of procrastination, identifying it as a strong predictor of procrastinatory behavior. This suggests that individuals with higher self-regulatory abilities are less likely to engage in procrastination, whether active or passive. The study also highlights differences in how self-regulation affects active versus passive procrastination, offering deeper insights into the mechanisms underlying these behaviors. These results contribute to a better understanding of the dynamics between self-regulation and procrastination in academic settings. Moreover, the study provides a valuable framework for designing targeted interventions aimed at enhancing self-regulatory skills among higher education faculty. Such interventions can potentially reduce procrastination, thereby improving the efficiency and effectiveness of the teaching and learning process. Overall, the research emphasizes the importance of strengthening self-regulation to mitigate procrastinatory tendencies in academic professionals, supporting improved educational outcomes.